Preparation of nanoscale LaXO3 (X=Co, Mn, Ni) by rheological phase method for oxygen reduction reaction. Issue 2 (15th January 2023) - Wang, Pan; Fu, Ce; Zhan, Wei; Zhang, Rong-Hua; Yan, Luo-Yi; Cheng, Zheng; Zhang, Xin; Zhou, Xin-Wen
Abstract: The rheological phase method(RPM) is a simple and environmentally friendly synthesis method. In this work, nanoscale LaXO3 (X = Co, Mn, Ni) series catalysts have been synthesized by RPM and their oxygen reduction reaction (ORR) have been investigated. The optimal calcination temperature of the RPM is lower than that of the solid-phase method, and the catalytic activity of the catalyst is also higher than that of solid-phase method, mainly because the products prepared by RPM have a nanoscale porous structure and a small amount of residual carbon. By comparing the differences among LaCoO3, LaMnO3, and LaNiO3, the results show that the ORR activity of the catalyst is the strongest when the b-site element is Mn, and the calculated electron transfer number is 3.99, which is close to 4 electrons, indicating that the by-product generation is relatively small, and the kinetic current density reach 6.63 mA cm −2 . Both were higher than of LaCoO3 and LaNiO3 . This work is expected to provide a new green synthesis method for non-noble metal catalyst perovskite oxygen reduction catalyst of LaCoO3, LaMnO3, and LaNiO3 .